2018
DOI: 10.1016/j.msea.2018.02.046
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelasticity of Cu- and La-based bulk metallic glasses: Interpretation based on the quasi-point defects theory

Abstract: The dynamic mechanical relaxation of metallic glasses is closely associated with the physical and mechanical properties. In the current work, the dynamic mechanical relaxation behaviors of Cu46Zr45Al7Y2 and La65Al14(Cu5/6Ag1/6)11(Ni1/2Co1/2)10 bulk metallic glasses are investigated by mechanical spectroscopy. In general, metallic glasses display two relaxation modes: main ( ) relaxation and the slow secondary ( ) relaxation. The α relaxation is linked to the dynamic glass transition phenomenon and viscous flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 48 publications
2
3
0
Order By: Relevance
“…Figure 7 also shows that the exponent is in the range of 0.5, as also reported in other works related to glassy alloys [43]. For Advances in Materials Science and Engineering evaluation of dynamic mechanical behavior of MGs, it is also possible to apply the theory of quasi-point defects (QPDs) [44]. In this theory, the defect concentration of glassy structure is quantified and correlated to the normalized loss modulus:…”
Section: Resultssupporting
confidence: 66%
“…Figure 7 also shows that the exponent is in the range of 0.5, as also reported in other works related to glassy alloys [43]. For Advances in Materials Science and Engineering evaluation of dynamic mechanical behavior of MGs, it is also possible to apply the theory of quasi-point defects (QPDs) [44]. In this theory, the defect concentration of glassy structure is quantified and correlated to the normalized loss modulus:…”
Section: Resultssupporting
confidence: 66%
“…By the same method, the activation energy E  of Zr50Cu34Ag8Al8 is 5.858 eV. The result is in good agreement with other CuZr-based metallic glass systems [38,41] .This value of the apparent activation energy of the -relaxation in the super-cooled liquid region corresponds to a liquid fragility of 𝑚 43.…”
Section: Isochronal Analysessupporting
confidence: 78%
“…The loss factor, tan𝐸"/𝐸 , is related to the atomic or molecular mobility of glassy materials [38] .…”
Section: Isochronal Analysesmentioning
confidence: 99%
“…Its characteristic time decreases following the Arrhenius law as temperature increases, eventually becoming undetectable at the experimental timescale. We also observed that the stress decay caused by the  relaxation during deformation is only about 5%, which is far less than the anelastic component (>30%) of the amorphous solids in some previous literature [28,41]. Therefore, part of the anelastic component should be derived from the contribution of the second deformation process controlled by the  relaxation.…”
mentioning
confidence: 47%